Apricot (Prunus armeniaca L.) drought resistance and its connection with thickness of leaf blade - В. В. Корзін; В. М. Горіна; О. А. Ільницький; В. А. Одинцова (Plant Varieties Studying and Protection)
The studying results of drought resistance for 15 varieties and 6 forms of apricot in the condition of South of the Ukraine have been given. The plants with different level of drought resistance have been selected from apricot varieties and forms introduced on the South Coast of the Crimea. From the studied varieties the most drought resistance ones are: Vardaguin Vagdaas, Luchak Sumbarskiy, Sulina, LE-132. Two best apricot varieties have been recommended for use in selection on this character